A decision support system for placement and transfer of teachers - Abdul Rahman, Azizah; Wang, Chih Fong (2005)
One of the core functions of HRM is about assigning the right people to the right post. With changing organization and personal needs as time goes by, location and relocation of personnel can be an on going exercises in an organization. In Malaysia, teacher and school is a part of the public service. With centralized administration and life long employment, matching organization needs with personnel requirements through recruitment, placement and transfer is a challenge. For education, matching teachers with the right academic qualifications and subjects taught is crucial to ensure quality education in school. The District Education Office (DEO) plays a crucial role in matching available teacher resources with subject-teacher vacancies available in schools. DEO needs to ensure that schools have enough teachers with the right options, but at the same time, take care of the welfare of teachers by placing them in their preferred schools. The two needs were satisfied through two separate but mutually influencing processes, i.e. transfer and placement of teachers. The purpose of this paper is to discuss the use of decision models and IT to facilitate the matching process. The paper compares the use of weighting methods, sequential elimination by conjunctive constraints and sequential elimination by Lexicography, and in making the decision.